2005
DOI: 10.1016/j.ijdevneu.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins in murine viscera: a dynamic pattern from birth to adulthood

Abstract: There is growing evidence that target-derived neurotrophins regulate the function of visceral neurons after birth. However, the postnatal profile of neurotrophin supply from internal organs is poorly described. In this study, we compared neurotrophin concentrations in lysates of murine peripheral target tissues (lung, heart, liver, colon, spleen, thymus, kidney and urinary bladder) at different time points after birth. In most organs, there was a decrease of neurotrophin concentrations in the first weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 48 publications
0
41
0
3
Order By: Relevance
“…Despite the name, BDNF is expressed in most tissues of the body at relatively high levels (25). BDNF in the blood could be derived from a number of these peripheral tissues, as well as from the brain.…”
Section: What Is Source Of the Serum Bdnf?mentioning
confidence: 99%
“…Despite the name, BDNF is expressed in most tissues of the body at relatively high levels (25). BDNF in the blood could be derived from a number of these peripheral tissues, as well as from the brain.…”
Section: What Is Source Of the Serum Bdnf?mentioning
confidence: 99%
“…The relevance of such effects lies in the recent recognition that circulating and local BDNF concentrations, as well as receptor expression, are increased in asthma (22,44). Furthermore, animal studies suggest a role for BDNF in airway inflammation, remodeling, and hyperreactivity (47,48).…”
Section: Neurotrophins and Asmmentioning
confidence: 99%
“…The BDNF, acting throughout TrkB, seems to participate in the inflammatory processes including the activation of macrophages . Interestingly, detectable levels of the two main TrkB ligands, the BDNF and NT-4/5 (Lommatzsch et al , 2005Nemoto et al 2000;Cassiman et al 2001) are also present in the liver, and did not change significantly during the postnatal live (Lommatzsch et al 2005), suggesting the possibility of paracrine and/or autocrine intrahepatic loops. Thus, it could be hypothesized that the persistence of erythroblastric islands in TrkB deficient animals might be due to an impaired ability of macrophages to remove and eliminate these structures due to their not being responsive to NTs.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, data about the expression of TrkB and its main ligands in this organ are scarce and unclear. Thus, RT-PCR on human and rat liver showed trace levels of TrkB (Yamamoto et al 1996;Nemoto et al 2000), BDNF, and NT-4/5 (Lommatzsch et al , 2005Nemoto et al 2000;Cassiman et al 2001). On the other hand, results from immunohistochemical studies are contradictory; whereas some authors (Shibayama and Koizumi 1996) were unable to detect any Trk in the human liver, others (Cassiman et al 2001) observed TrkB immunostaining in human and rat hepatic stellate cells (although RT-PCR failed to demonstrate mRNA transcripts for TrkB in freshly isolated rat hepatic stellate cells), in normal and pathological conditions (Cassiman et al 2002).…”
Section: Introductionmentioning
confidence: 95%